Evaluation of interseeded grain sorghum and soybeans as a silage crop - Harbers, L.H.; Bolsen, K.K.; Hartadi, H. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Dry matter yield of grain sorghum alone averaged more than 1.0 ton per acre higher than that of intercropped grain sorghum-soybeans in both 1988 and 1989. All silage yields were lower in 1989 because of drought. Grain sorghum silage had less NDF and ADF, but intercropped silages had over 4 percentage units more crude protein. Digestibility coefficients for crude protein, NDF, and ADF tended to favor intercropped silages, but yearling steer performance favored grain sorghum silage. Studies over 4 years (1986 to 1989) suggest that intercropping might be more beneficial for dairy cattle producers than beef producers.
Keywords: Beef; Grain sorghum; Soybeans; Intercrop; Silage